Beyond the network. A critical inquiry into the limits of the actor-network theory - Mladenović Ivica (Glasnik Etnografskog Instituta SANU, 2025)
This article critically examines the limitations and challenges of Actor- Network Theory (ANT) in contemporary social theory. Originally developed as a response to structuralist and constructivist paradigms, ANT offered a radical methodological alternative, emphasizing actor-relationality and emergent networks over predefined so-called social structures. While this approach has significantly shaped disciplines such as Science and Technology Studies (STS), political sociology, and environmental governance, it has also faced sustained criticism. Critics argue that ANT’s refusal to engage with structural determinants, macro-political constraints, and historical asymmetries limits its explanatory power, particularly in relation to domination, hierarchy, and systemic inequalities. This article explores whether ANT can evolve beyond its descriptive commitments to address these concerns without compromising its core principles. Through an analysis of power asymmetries, digital governance, and ecological crises, the article interrogates whether ANT can reconcile empirical inquiry with critical engagement. Ultimately, it argues that ANT’s future depends on its ability to navigate the tension between methodological openness and theoretical reflexivity, raising broader questions about the limits of a theory that seeks to expand beyond the very epistemological constraints that define it.